1999
DOI: 10.1152/jn.1999.82.5.2490
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Contour Features in Macaque Area V4

Abstract: The ventral pathway in visual cortex is responsible for the perception of shape. Area V4 is an important intermediate stage in this pathway, and provides the major input to the final stages in inferotemporal cortex. The role of V4 in processing shape information is not yet clear. We studied V4 responses to contour features (angles and curves), which many theorists have proposed as intermediate shape primitives. We used a large parametric set of contour features to test the responses of 152 V4 cells in two awak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
362
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(407 citation statements)
references
References 44 publications
41
362
4
Order By: Relevance
“…It is well known that many V4 neurons are selective for color and/or orientation even when the stimulus in the receptive field is irrelevant to the current behavior (9,12,32). Feature attention enhances preexisting feature selectivity when the monkey is searching for a target with a feature for which the neuron is selective (2).…”
Section: Causes Of the Difference In V4 Responses In The Search And Smentioning
confidence: 99%
“…It is well known that many V4 neurons are selective for color and/or orientation even when the stimulus in the receptive field is irrelevant to the current behavior (9,12,32). Feature attention enhances preexisting feature selectivity when the monkey is searching for a target with a feature for which the neuron is selective (2).…”
Section: Causes Of the Difference In V4 Responses In The Search And Smentioning
confidence: 99%
“…The 2-s presentation was selected because we want to eliminate accommodation effects and assure enough time for steady fixation. We had already observed that deliberate fixation at the borders increased thresholds (15). The order of the stimulus pair was randomly selected.…”
Section: Methodsmentioning
confidence: 99%
“…However, these investigators do not address this specific theory. Other physiological studies have used traditional sine wave gratings, checkerboard-like stimuli or complex form stimuli (11)(12)(13) as well as faces and hands (14) to investigate cell responses from striate cortex to higher visual areas (15,16). Pasupathy and Connor (15) measured cell responses to angles and found "strong bias towards" responses to convex angles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is conceivable that V1 may represent photographs and line drawings in a similar way. Visual areas V2, VP (known as V3v, for ventral V3, in some nomenclatures), and V4 are of interest because they build more complex representations based on the information in V1, including representations that rely on more global aspects of the image (16)(17)(18). The PPA and the RSC, which have been shown to prefer scenes over objects and other visual stimuli (19,20), are of interest in this analysis because they (and, to some extent, the LOC) contain information about scene category in their activity patterns that are closely linked to behavioral scene-categorization performance (12).…”
mentioning
confidence: 99%